Staged Surgical Correction of Severe Panfacial and Transverse Nasal Root Asymmetry in Unicoronal Synostosis. Issue 5 (20th May 2022) - Witherow, Helen; Pepper, Tom; Naini, Farhad B.
Abstract : Summary: Nasal asymmetry is widely acknowledged to be one of the most difficult deformities to manage. Most reports in the literature pertain to corrective methods in relation to isolated deformity of the dorsum in the posttraumatic patient. There is a paucity of literature relating to management of nasal radix asymmetry, and still less in the context of severe panfacial asymmetry.